Curriculum responsiveness within the context of decolonisation in South African higher education - Fomunyam, Kehdinga George; Teferra, Damtew (Faculty of Education, University of the Free State, 2017)
South African higher education in the past year has seen violent calls for decolonisation of the curriculum, as a way of addressing the passive nature of education. The inability of the curriculum to respond to contextual issues, empower students to come of age, while at the same time remain committed to giving them a plurality of voices has been a cause for concern. Morrison (2007) argues that curriculum discourse should be marked by a multiplicity of voices, articulating a hundred thousand theories thereby creating avenues for a just and caring curriculum. This curriculum is only possible in spaces that are open to construction and reconstruction of responsive knowledge. To enhance the responsiveness of the curriculum, this paper experimented on voices that matter in the decolonisation project in the bid to create sustainable and socially just spaces wherein caring and just curriculum encounters can take place. Designed as a qualitative case study of six universities, the study used open-ended questionnaires and semi-structured interviews to generate data. The data generated was analysed using Morrison’s (2007) notion of a hundred thousand theories. The paper reveals three key findings: curriculum encounters are shaped by power dynamics in educational spaces, plurality of voices provokes the creation of disciplinary and interdisciplinary spaces for curriculum engagement and sustainable education experience is powered by plurality, which in itself is shaped by curricular charges. The paper concludes that curriculum encounters is vital for the effectiveness of the decolonisation process and the enhancement of curriculum responsiveness.
Keywords: Curriculum encounters; Responsiveness; Decolonisation; Plurality